Science Behind Homoeopathic Pharmacy-Part 1 Preparation of Mother Tincture (Homoeopathy for All, 2024)
In Homoeopathic curriculum,  Pharmacy is no doubt the most  neglected subject, in spite of the  fact that without understanding  the principle and science behind  preparation of homoeopathic  medicines, it is not possible to get  good medicine and it is also not  very difficult to understand that if  the physicians do not get quality  medicine, all their effort of treating  a patient will fail. Medicines  are regarded as weapons in the  hand of the physicians and if the  weapon is blunt how they can  fight successfully against diseases.  Dr. Hahnemann advocated that  medicines should be prepared by the  physicians themselves so that they  get the best quality weapon to fight  against the ailments, but under the  current socio-economic condition  it is not practical for the physicians  to prepare medicines themselves  for treatment and they are required  to depend on the pharmaceutical  manufacturers for getting good  quality medicines. Here the  question arises if the manufacturers,  even after employing BHMS  qualified physicians for production  of medicines, are able to produce  quality homoeopathic medicines,  do they understand the science of  making medicine or they are just  doing all these things mechanically.
Keywords: Science; Homoeopathic